Review of the genus Engyprosopon Günther, 1862 (Pleuronectiformes: Bothidae) from waters off Taiwan, with descriptions of two new species - Amaoka, Kunio; Ho, Hsuan-Ching (Zootaxa, 2018)
Species of the bothid genus Engyprosopon Günther, 1862 from the waters off Taiwan are reviewed. Nine species are recognized and described. Of the nine species, E. grandisquama (Temminck & Schlegel, 1846), E. multisquama Amaoka, 1963 and E. maldivense (Regan, 1908) previously known from Taiwan are confirmed, whereas E. xystrias Hubbs, 1915, E. mogkii (Bleeker, 1854), E. longipelvis Amaoka, 1969 and E. mozambiquense Hensley, 2003 represent new records for Taiwan. Moreover, two further species are described new to science. Engyprosopon brevifrontale sp. nov. is characterized by a deep and short body, large eyes situated close to the head margin, 0 + 9–10 smooth gill rakers, strong rostral and upper orbital spines on the ocular side, small rostral spine on the blind side, and a dark blue peritoneum. Engyprosopon parvipectorale sp. nov. is characterized by the combination of serrate gill rakers, large head (3.1–3.4 in SL); extremely narrow or almost ridge-like interorbital in both sexes; ocular-side pectoral fin distinctly short (1.4–1.6 in HL) in both sexes; and no rostral or orbital spines in either sex. Detailed descriptions and a key to all of the species of Engyprosopon recorded from the waters off Taiwan are provided.